2018
DOI: 10.31539/costing.v2i1.388
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Faktor Demografi terhadap Literasi Keuangan

Abstract: Financial knowledge is one of the important aspects in life today. This study aims to determine the level of financial literacy in motorbike workshop SMEs in Kec.Siak Hulu Kab. Kampar and analyze whether demographic factors consisting of education level, income level, duration of business and age affect the level of financial literacy among workshop entrepreneurs. The number of samples in this study are 50 workshop entrepreneurs with the research method used is the survey method by obtaining data through quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Secara keseluruhan responden pada penelitian ini memiliki latar pendidikan yang memadai serta pada rentang usia produktif. Hal tersebut termasuk diantara faktor pendukung dalam membentuk tingkat literasi pada masyarakat dari sisi demografi sosial sebagaimana temuan pada kajian-kajian terdahulu Bhushan & Medury (2013), Mbarire & Ali (2014), Yusnita & Abdi (2018, dan Dewanty & Isbanah (2018, yang menyimpulkan bahwa masyarakat dengan latar pendidikan yang memadai cenderung lebih mudah terpapar dengan informasi-informasi seputar keuangan.…”
Section: Hasil Dan Pembahasanunclassified
“…Secara keseluruhan responden pada penelitian ini memiliki latar pendidikan yang memadai serta pada rentang usia produktif. Hal tersebut termasuk diantara faktor pendukung dalam membentuk tingkat literasi pada masyarakat dari sisi demografi sosial sebagaimana temuan pada kajian-kajian terdahulu Bhushan & Medury (2013), Mbarire & Ali (2014), Yusnita & Abdi (2018, dan Dewanty & Isbanah (2018, yang menyimpulkan bahwa masyarakat dengan latar pendidikan yang memadai cenderung lebih mudah terpapar dengan informasi-informasi seputar keuangan.…”
Section: Hasil Dan Pembahasanunclassified
“…There are differences in research results related to demographic factors that affect financial literacy. Yusnita & Abdi (2018), in their research, found that the literacy level of the microenterprises they studied was still low. The results showed that income level had a significant effect on financial literacy, while age, education level, and length of business did not have a significant effect.…”
Section: Financial Literacymentioning
confidence: 93%
“…Individual perspectives also include beliefs. a person's ability to be successful and deal with financial problems as well as possible; this is often referred to as self-efficacy [9,10].…”
Section: Demographic Factorsmentioning
confidence: 99%